Left atrial thrombus and smoke resolution in patients with atrial fibrillation or flutter under chronic oral anticoagulation. (19th May 2022) - Di Cori, A; Barletta, V; Meola, L; Carluccio, M; Branchitta, G; Cellamaro, T; Parollo, M; Mazzocchetti, L; Gentile, F; Segreti, L; Viani, S; De Lucia, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Data on left atrial/left atrial appendage (LA/LAA) thrombus resolution after non–vitamin K antagonist (VKA) oral anticoagulant treatment (OAT) are scarce. Purpose: The aim of this study was to explore retrospectively the resolution of LA/LAA spontaneous echo-contrast or thrombus in patients with nonvalvular atrial fibrillation (AF) or atrial flutter (AFL) after OAT in a real-world single center practice. Methods: A single center retrospective analysis of patients with AF/AFL who underwent a transesophageal echocardiography (TEE) for an electrical cardioversion and/or atrial fibrillation ablation was performed. Patients showing LA/LAA echo-contrast or thrombus and with at least one TEE follow up to detect the resolution of LA/LAA echo-contrast/thrombus were included and analyzed. Results: Among 277 TEE performed, 73 cases (26%) of LA/LAA echo-contrast or thrombus were detected in our hospital. Among them, a total of 53 patients showed LAA/LA echo-contrast (19%) and 20 (7%) patients showed a thrombus. Patients with echo-contrast or thrombus were usually male (78% vs 72%, p=0.05) with more comorbidities, as hypertension (90% vs 72%, p=0.03) and congestive heart failure (36% vs 17%, p=0.007) and with an overall higher CHA2DS2-Vasc score (3.5±1.5 vs 3±1, p=0.0001). All they were under chronic anticoagulation with a VKA (65%) or with a NOAC (35%), without differences between groups. (p=NS). At the TTE/TEE analysis, they showed a comparable ejection fraction (55±11 vs 55±22%, p=NS), a trend for an increased LA dilatation (27±8 vs 26±6 cm2, p=0.07) and a low LAA peak velocity (94% vs 19%, p=0.0001). The Echo-contrast Group maintained the same OAT strategy in 49 patients (93%), switching from VKA to NOAC in 3 cases (6%) and from NOAC to NOAC in 1 (1%). The Thrombus Group kept the same OAT strategy with a NOAC in 6 cases (30%) and changed the strategy in 14 patients (70%). Particularly, they titrated NOAC dose in 1 (5%) and the VKA dose in 4 (20%), switched from NOAC to VKA in 5 (25%), from VKA to NOAC in 3(15%) and from NOAC to NOAC in 1 (5%). Smoke resolution was observed in LA/LAA smoke group in 1/10 cases (10%) after a median time of 52 days (20-135) and LA/LAA thrombus resolution 8/15 (53%) after a median time of 45 days (25-180). Patients with the thrombus resolution had a lower CHA2DS2-Vasc score (3.5±2 vs 4±1, p=0.05), and showed a trend for a more frequent use of a NOAC (37.5 vs 28%, p=0.07) and a longer overall anticoagulation time (7.5 vs 4 months, p=0.08). At one-year follow-up, 1 ischemic stroke (1.9%) and 2 deaths (3.8%) were observed only in the Echo-contrast group. Conclusion(s): In OAT patients with an LA/LAA thrombus changing the OAT strategy is associated with thrombus resolution in more than 50% of cases, after an appropriate anticoagulation period and in lower CHAD2S2Vasc patients. Chronic OAT strategy confirmation, also with NOAC, is rarely effective, also in case of echo-contrast resolution.